Agreement and Correlation Between the Straight Leg Raise and Slump Tests in Subjects With Leg Pain - Walsh, J.; Hall, Toby (Elsevier Inc, 2009)
Objective: The straight leg raise (SLR) and slump tests have traditionally been used to identify nerve root compression arising from disk herniation. However, they may be more appropriate as tests of lumbosacral neural tissue mechanosensitivity. The aim of this study was to determine agreement and correlation between the SLR and slump tests in a population presenting with back and leg pain. Methods: This was an observational, cross-sectional study design. Forty-five subjects with unilateral leg pain were recruited from an outpatient Back Pain Screening Clinic at a large teaching hospital in Ireland. The SLR and slump tests were performed on each side. In the event of symptom reproduction, the ankle was dorsiflexed. Reproduction of presenting symptoms, which were intensified by ankle dorsiflexion, was interpreted as a positive test. An inclinometer was used to measure range of motion (ROM). Results: There was substantial agreement between SLR and slump test interpretation (? = 0.69) with good correlation in ROM between the 2 tests (r = 0.64) on the symptomatic side. In subjects who had positive results, ROM for both tests was significantly reduced compared to ROM on the contralateral side and ROM in subjects who had negative results. Conclusions: When the SLR and slump tests are interpreted as positive in the event of reproduction of presenting leg pain that are intensified by ankle dorsiflexion, these tests show substantial agreement and good correlation in the leg pain population. When interpreted in this way, these tests may be appropriate tests of neural tissue mechanosensitivity, but further criteria must be met before a definitive conclusion in relation to neural tissue mechanosensitivity may be drawn. © 2009 National University of Health Sciences.